Shared genetic effects between hepatic steatosis and fibrosis: A prospective twin study - Cui, Jeffrey; Chen, Chi‐Hua; Lo, Min‐Tzu; Schork, Nicholas; Bettencourt, Ricki; Gonzalez, Monica P.; Bhatt, Archana; Hooker, Jonathan; Shaffer, Katherine; Nelson, Karen E.; Long, Michelle T.; Brenner, David A.; et al. (Hepatology (Baltimore, Md.), 2016)
Nonalcoholic fatty liver disease is associated with metabolic risk factors including hypertension and dyslipidemia and may progress to liver fibrosis. Studies have shown that hepatic steatosis and fibrosis are heritable, but whether they have a significant shared gene effect is unknown. This study examined the shared gene effects between hepatic steatosis and fibrosis and their associations with metabolic risk factors. This was a cross‐sectional analysis of a prospective cohort of well‐characterized, community‐dwelling twins (45 monozygotic, 20 dizygotic twin pairs, 130 total subjects) from southern California. Hepatic steatosis was assessed with magnetic resonance imaging‐proton density fat fraction and hepatic fibrosis with magnetic resonance elastography. A standard bivariate twin additive genetics and unique environment effects model was used to estimate the proportion of phenotypic variance between two phenotypes accounted for by additive genetic effects and individual‐specific environmental effects. Genetic correlations estimated from this model represent the degree to which the genetic determinants of two phenotypes overlap. Mean (± standard deviation) age and body mass index were 47.1 (±21.9) years and 26.2 (±5.8) kg/m2, respectively. Among the cohort, 20% (26/130) had hepatic steatosis (magnetic resonance imaging‐proton density fat fraction ≥5%), and 8.2% (10/122) had hepatic fibrosis (magnetic resonance elastography ≥3 kPa). Blood pressure (systolic and diastolic), triglycerides, glucose, homeostatic model assessment of insulin resistance, insulin, hemoglobin A1c, and low high‐density lipoprotein had significant shared gene effects with hepatic steatosis. Triglycerides, glucose, homeostatic model assessment of insulin resistance, insulin, hemoglobin A1c, and low high‐density lipoprotein had significant shared gene effects with hepatic fibrosis. Hepatic steatosis and fibrosis had a highly significant shared gene effect of 0.756 (95% confidence interval 0.716‐1, P < 0.0001). Conclusions: Genes involved with steatosis pathogenesis may also be involved with fibrosis pathogenesis. (Hepatology 2016;64:1547‐1558)